2016
DOI: 10.4236/fns.2016.710090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant-Based Antimicrobial Washes on Sensory Properties of Organic Leafy Greens

Abstract: The objective was to study the sensory attributes of organic leafy greens treated with plant antimicrobials and identify treatments most accepted by panelists. Organic leafy greens were washed with antimicrobials and stored at 4°C for 24 h prior to serving panelists. Antimicrobials evaluated include: 0.1% clove bud, lemongrass, oregano, or cinnamon essential oils; 0.1% carvacrol or citral; 3% grapeseed, apple, or 10%/7% olive extract; combination of essential oils with extracts; 3% hydrogen peroxide; and untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
4
7
0
Order By: Relevance
“…GSE has also been found to increase the red color of raw meat and retention of color in cooked meat due to the anthocyanins in GSE (Perumalla & Hettiarachchy, 2011). Joshi, Sparks, Friedman, and Ravishankar (2016) Ignat, Stingu, Volf, and Popa (2011) found that GSE may modulate plant growth in terms of pigment accumulation. The addition of GSE in the growth medium of rape and maize plants stimulated chlorophyll a, a form of chlorophyll that absorbs violet to red light and reflects green light (U.S. National Library of Medicine, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GSE has also been found to increase the red color of raw meat and retention of color in cooked meat due to the anthocyanins in GSE (Perumalla & Hettiarachchy, 2011). Joshi, Sparks, Friedman, and Ravishankar (2016) Ignat, Stingu, Volf, and Popa (2011) found that GSE may modulate plant growth in terms of pigment accumulation. The addition of GSE in the growth medium of rape and maize plants stimulated chlorophyll a, a form of chlorophyll that absorbs violet to red light and reflects green light (U.S. National Library of Medicine, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Joshi, Sparks, Friedman, and Ravishankar () investigated the sensory impact of GSE on lettuce and spinach. Based on color measurements using the International Commission on Illumination‐CIE L * a * b * color scale, GSE produced a slightly reddish color ( a * = 0.10 ± 3.0) for lettuce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instructions on how to order reprints of this article, please visit our website: www.emeraldgrouppublishing.com/licensing/reprints.htm Or contact us for further details: permissions@emeraldinsight.com NFS 45,4…”
Section: About the Authorsmentioning
confidence: 99%
“…The sensory panel consisted of 66 participants/panelists (Joshi et al, 2016) representing the different educated and non-educated categories in a ratio of 8:3 and their responses were taken three times at different points in time.…”
Section: Sensory Panelmentioning
confidence: 99%